High-performance pure organic magnetic composite material and preparation method thereof

By doping fullerenes into the poly(3-hexylthiophene) system and following treatment, a poly(3-hexylthiophene)/fullerene/4"-n-pentyl-4-cyanotriphene composite was prepared, which solved the problem of difficulty in developing pure organic magnets with excellent performance at room temperature in the prior art, and achieved high-performance room temperature ferromagneticity and air stability.

CN119505485AActive Publication Date: 2025-02-25SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411643630.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25
Estimated Expiration
2044-11-18

Smart Images

  • Figure CN119505485A_ABST
    Figure CN119505485A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance pure organic magnetic composite material and a preparation method thereof, the composite material uses poly (3-hexylthiophene) as an electron donor and uses fullerene as an electron acceptor to synthesize a poly (3-hexylthiophene) / fullerene composite charge transfer material. Then the poly (3-hexylthiophene) / fullerene / 4 '-n-pentyl-4-cyano terphenyl composite material is obtained through subsequent doping of the 4'-n-pentyl-4-cyano terphenyl and the poly (3-hexylthiophene) / fullerene / 4 '-n-pentyl-4-cyano terphenyl composite material. According to the method and the material adopted by the invention, the charge transfer degree and the solid structure orderliness between pure organic composite materials are enhanced, so that the composite material obtains high room-temperature ferromagnetism and Curie temperature, and the defects that an organic magnetic material is unstable in performance in air and low in Curie temperature are overcome. By compounding poly (3-hexylthiophene), fullerene and 4 '-n-pentyl-4-cyano terphenyl, the invention provides a novel method for preparing a high-magnetism pure organic component composite material which is simple to operate, orderly in solid structure accumulation and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of novel energy materials, and in particular to a high-performance pure organic magnetic composite material poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl and a preparation method thereof. Background Art

[0002] With the advancement of modern science and technology, magnetic materials have a wide range of application needs in the fields of electronic communications, information storage and life sciences. Traditional magnetic materials are mostly inorganic materials such as metals, alloys, minerals, etc. with 3d or 4f orbital electrons. However, due to their high specific gravity, hardness, complex synthesis process, easy corrosion and large magnetic loss, they can no longer meet the requirements of magnetic materials in some high-tech and cutting-edge technology fields. In recent years, with the continuous advancement of superconducting material preparation technology, the preparation of organic magnetic materials has attracted much attention. Organic magnets have the advantages of flexibility, light weight, low magnetic loss and good biocompatibility, and are expected to lead major technological innovations in aerospace, information, military industry and life sciences.

[0003] Pure organic magnetic materials refer to organic compounds composed of low-Z elements such as C, H, O, and N. Their magnetism comes from the long-range order of s and p orbital electron spins. The synthesis of high-spin organic magnets must meet the following two conditions: the presence of paramagnetic units (spins); and ferromagnetic interactions between spins. In the process of molecular synthesis, paramagnetic centers with unpaired electrons, including free radicals, solitons with spins, polarons, etc., are introduced into the main chain of the molecule to regulate the intermolecular interaction mode, so that the spins are arranged in order, thereby obtaining macroscopic ferromagnetism. Therefore, pure organic magnets have the characteristics of structural diversity, good stability, and strong plasticity, and can obtain multifunctional magnetic materials that combine optical, electrical, mechanical and other properties.

[0004] Common organic magnetic materials mainly include organic free radical polymers, high-spin cross-linked macromolecules, and spin-doped conjugated polymers. The magnetism of common free radical-containing organic magnets originates from the ferromagnetic exchange between the main chain carbon atoms and the side chain free radicals, but their chemical properties are active and they will completely lose their magnetism after being exposed to the air for a few seconds. Moreover, such organic magnets usually show magnetism only at extremely low temperatures. Ovchinnikov reported the first experimental synthesis of pure organic magnet poly-1,4-bis(2,2,6,6-tetramethyl-4-hydroxy-1-oxy-piperidine) diacetylene (abbreviated as polyBIPO), which broke the conclusion that organic materials are magnetically insulating. However, Fang Zhong and others found in the experiment that although some free radicals show magnetism due to the presence of lone pairs of electrons, their chemical properties are active. Only under sufficiently stable conditions can the free radicals be prepared, separated and characterized. Moreover, due to the natural chemical activity of free radicals, the reported organic ferromagnets are usually unstable and will completely lose their magnetism after being exposed to the air for a few seconds.

[0005] Reasonable molecular design is an important step in obtaining a stable organic π-conjugated magnetic framework in order to stabilize its spin center and maintain a high magnetic order state. Rajca et al. alternately connected free radical modules with different spin quantum numbers and high cross-linking density to synthesize a conjugated polymer with a large magnetic moment. However, the magnetism of this material is only stable when the temperature is below 10K, which is difficult to meet practical standards. Phan et al. found that in a covalently linked porous organic free radical framework, adjacent free radicals are ferromagnetically coupled. The 1,3,5-triazine chain porous organic free radical framework obtained by heat or slightly acid-assisted polymerization exhibits spontaneous magnetization and hysteresis at room temperature, and the ordering temperature reaches above 450K. Mahmood et al. reported a room-temperature ferromagnetic triazine network polymer formed by the self-polymerization of 7,7,8,8-tetracyanoquinoline dimethane (TCNQ). Its glassy state can capture highly stable free radicals generated by spins, thus making the polymer present ferromagnetic order. Purposeful spin assembly and regulation through structural design is an effective way to obtain pure organic magnets, but problems such as difficulty in synthesis, poor repeatability and low yield remain to be solved.

[0006] In addition to the above-mentioned free radical compounds, some classic conjugated polymers, such as polyaniline, polypyrrole, regio-irregular poly(3-alkylthiophene) and substituted polyacetylene, also show ferromagnetism after doping. Paula synthesized ClO by electrochemical method. 4- Doped metal-free magnetic P3TH, the charge transfer caused by doping produces polarons with unpaired electrons, which is the key to ferromagnetism. Yang et al. prepared a composite exciton solution by mixing P3HT and PCBM, and its film showed strong room temperature ferromagnetism with a saturation magnetization of about 0.65emu / g. Vandeleene et al. reported the magnetism of neutral (undoped) polythiophene with different side chains, especially exploring the effects of substituent properties, substitution patterns and regional regularity on magnetism. However, since the spin distance is too large, spin coupling cannot be carried out, so the magnetism is very weak. So far, pure organic magnets with excellent performance and stability at room temperature have not been found in organic materials composed only of C, H, O, N, etc.

[0007] Based on the above analysis, a pure organic magnetic material with excellent room temperature ferromagnetism and air stability is urgently needed in this industry. Summary of the invention

[0008] The purpose of the present invention is to solve the above problems existing in the prior art and provide a high-performance pure organic magnetic composite material and a preparation method thereof. The present invention preassembles poly(3-hexylthiophene) powder in a mixed solvent; then dopes fullerene in the poly(3-hexylthiophene) system to form a charge transfer complex; and finally post-treats 4″-n-pentyl-4-cyanoterphenyl to prepare a poly(3-hexylthiophene) / fullerene / 4″-n-pentyl-4-cyanoterphenyl composite material. The composite material is a pure organic magnetic composite material with excellent room temperature ferromagnetism and air stability.

[0009] The technical solution adopted by the present invention is as follows: A method for preparing a high-performance pure organic magnetic composite material comprises the following steps:

[0010] S1, pre-treating poly(3-hexylthiophene) powder, o-dichlorobenzene and acetonitrile with a solvent to obtain a poly(3-hexylthiophene) solution, and then adding fullerene to obtain a mixed solution;

[0011] S2, prepare a silicon wafer substrate, and clean the silicon wafer with a polar solvent; drop the mixed solution in S1 on the cleaned silicon wafer substrate, cover it with a watch glass, and slowly dry it to obtain a poly (3-hexylthiophene) / fullerene composite charge transfer film;

[0012] S3: The poly(3-hexylthiophene) / fullerene composite charge transfer film obtained in S2 is subsequently doped with 4"-n-pentyl-4-cyanoterphenyl to obtain a poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite material.

[0013] Preferably, in S1, the poly(3-hexylthiophene) powder is dissolved in o-dichlorobenzene, and the mixture is ultrasonically dissolved and mixed to obtain a poly(3-hexylthiophene) / o-dichlorobenzene solution, and acetonitrile is added to obtain a poly(3-hexylthiophene) solution.

[0014] Preferably, the poly(3-hexylthiophene) powder has a purity of 95-99%.

[0015] Preferably, the concentration of the poly(3-hexylthiophene) / o-dichlorobenzene solution is 5 to 50 mg / mL.

[0016] Preferably, the volume ratio of the acetonitrile to the poly(3-hexylthiophene) / o-dichlorobenzene solution is 5%-25%.

[0017] More preferably, the mass ratio of the poly(3-hexylthiophene) powder to the fullerene in S1 is 10:1 to 1:1.

[0018] More preferably, the polar solvent in S2 is one of ethanol, isopropanol and acetone.

[0019] More preferably, the volume ratio of the poly(3-hexylthiophene) / fullerene composite charge transfer film to 4"-n-pentyl-4-cyanoterphenyl in S3 is 1:1 to 1:10.

[0020] The present invention also provides a high-performance pure organic magnetic composite material prepared by the above preparation method, wherein the high-performance pure organic magnetic composite material is a poly (3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite material.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention prepares a pure organic magnetic composite material, namely, a poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite material. In the ternary composite material, the closed shell structure of the poly(3-hexylthiophene) system is broken by regulating charge transfer, and a pure spin density is obtained, and 4"-n-pentyl-4-cyanoterphenyl is used to improve the order of the molecular chain and enhance the crystallinity of the film, thereby effectively enhancing the room temperature ferromagnetism and air stability of the composite material.

[0023] 2. The preparation method of the composite material in the present invention has mild conditions, simple steps and rapid reaction, and can stably obtain a pure organic magnetic composite material with excellent room temperature ferromagnetism and air stability, which is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a digital photo image of poly(3-hexylthiophene) solution B in Example 3 of the present invention;

[0025] Figure 2 The Raman spectra of poly(3-hexylthiophene), fullerene and poly(3-hexylthiophene) / fullerene charge transfer complex in Example 3 of the present invention;

[0026] Figure 3 The infrared spectra of the composite films of 4"-n-pentyl-4-cyano terphenyl, poly(3-hexylthiophene) / fullerene and poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl in Example 3 of the present invention;

[0027] Figure 4 XRD spectra of poly(3-hexylthiophene) / fullerene and poly(3-hexylthiophene) / fullerene / 4″-n-pentyl-4-cyanoterphenyl composite films in Example 3 of the present invention;

[0028] Figure 5 Magnetic hysteresis loops of the poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite film newly prepared and placed in air for 3 months in Example 3 of the present invention. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0030] Example 1

[0031] Weigh poly(3-hexylthiophene) powder P3HT with a purity of 95% and dissolve it in o-dichlorobenzene solvent. Ultrasonic dissolution and mixing are performed to obtain 5 mg / mL poly(3-hexylthiophene) / o-dichlorobenzene solution A. Then, a certain amount of acetonitrile (V CAN :V o-DCB =5%), and after being uniformly mixed by ultrasonic treatment, the mixture was allowed to stand at room temperature to obtain a poly(3-hexylthiophene) solution B.

[0032] A certain amount of fullerene was added to solution B, with a mass ratio of fullerene to poly(3-hexylthiophene) of 1:1.5. After ultrasonic treatment and uniform mixing, the mixture was allowed to stand at room temperature to obtain poly(3-hexylthiophene) / fullerene solution C. The silicon wafer substrate was ultrasonically washed in acetone for 5 minutes, and then dried at low temperature in a vacuum oven for later use. Solution C was drop-coated on a clean substrate, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene composite charge transfer film D.

[0033] A volume of 1 ml of 4"-n-pentyl-4-cyano terphenyl was used for subsequent doping, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film.

[0034] Example 2

[0035] P3HT powder with a purity of 95% was weighed and dissolved in o-dichlorobenzene solvent, and then ultrasonically dissolved and mixed to obtain 8 mg / mL poly(3-hexylthiophene) / o-dichlorobenzene solution A. Then, a certain amount of acetonitrile (V CAN :V o-DCB =7%), and after being uniformly mixed by ultrasonic treatment, the mixture was allowed to stand at room temperature to obtain a poly(3-hexylthiophene) solution B.

[0036] A certain amount of fullerene was added to solution B, with a mass ratio of fullerene to poly(3-hexylthiophene) of 1:1. After ultrasonic treatment and uniform mixing, the mixture was allowed to stand at room temperature to obtain poly(3-hexylthiophene) / fullerene solution C. The silicon wafer substrate was ultrasonically washed in anhydrous ethanol for 5 minutes, and then dried in a vacuum oven at low temperature for later use. Solution C was drop-coated on a clean substrate, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene composite charge transfer film D.

[0037] A volume of 1.5 ml of 4"-n-pentyl-4-cyano terphenyl was used for subsequent doping, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film.

[0038] Example 3

[0039] P3HT powder with a purity of 99% was weighed and dissolved in o-dichlorobenzene solvent, and then ultrasonically dissolved and mixed to obtain a 5 mg / mL poly(3-hexylthiophene) / o-dichlorobenzene solution A. Then, a certain amount of acetonitrile (V CAN :V o-DCB =15%), and after being mixed evenly by ultrasonic treatment, the mixture was allowed to stand at room temperature to obtain poly(3-hexylthiophene) solution B, which was dark red. Figure 1 is a digital photograph image of solution B prepared in this example.

[0040] A certain amount of fullerene was added to solution B, with a mass ratio of fullerene to poly(3-hexylthiophene) of 1:2.5. After ultrasonic treatment and uniform mixing, the mixture was allowed to stand at room temperature to obtain poly(3-hexylthiophene) / fullerene solution C. The silicon wafer substrate was ultrasonically washed in acetone and isopropyl ketone for 5 minutes at a time, and then dried in a vacuum oven at low temperature for later use. Solution C was drop-coated on a clean substrate, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene composite charge transfer film D.

[0041] Figure 2 The Raman spectra of poly(3-hexylthiophene), fullerene and poly(3-hexylthiophene) / fullerene charge transfer complex in this example are shown in Figure 2. The Raman spectra excitation wavelength is 532nm. Fullerene has 1421, 1471 and 1574cm -1 Characteristic peaks. In composite film D, the characteristic Raman peaks of fullerene all disappeared. The negative charge of fullerene leads to a decrease in the concentration of neutral molecules, and the electrical characteristics of fullerene molecules are relatively dispersed, which is covered by the strong signal peak of P3HT. 1350~1500cm -1 The spectrum is very sensitive to the conjugation length and π electron delocalization degree of the molecular chain

[31] . -1 and 1450cm -1 They are the intra-ring CC and C=C stretching vibration peaks, respectively. Compared with poly(3-hexylthiophene), the intensity of the Raman peak related to poly(3-hexylthiophene) in composite film D is significantly increased, and the corresponding half-height width is reduced. The intensity of the Raman spectrum is proportional to the square of the induced dipole moment. This phenomenon indicates that there is an effective charge transfer between poly(3-hexylthiophene) and fullerene in film D, which affects the properties of the C=C bond and the charge distribution of the S element.

[0042] A 2 ml volume of 4"-n-pentyl-4-cyano terphenyl was used for subsequent doping, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film.

[0043] Figure 3 ] is the infrared spectra of 4"-n-pentyl-4-cyano terphenyl, poly (3-hexylthiophene) / fullerene and poly (3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film in this embodiment. Compared with (3-hexylthiophene) / fullerene, poly (3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film I 1510 / I 1460 The increase in the ratio indicates that 4”-n-pentyl-4-cyanoterphenyl helps to enhance the conjugated order of the molecular chains of the composite film. Figure 4 The XRD spectra of the poly(3-hexylthiophene) / fullerene and poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite films in Example 3 of the present invention. After being doped with 4"-n-pentyl-4-cyano terphenyl, the crystalline order of the composite film is significantly improved, and the π-π stacking distance of the poly(3-hexylthiophene) molecular chain is shortened, which is conducive to more efficient charge transfer and more stable and stronger polaron spin coupling, and is the key to the high magnetization intensity of the poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film. The poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film was exposed to air for three months, and the magnetic properties of the film after aging were characterized to explore the effect of external conditions on magnetism. Figure 5 : The hysteresis loops of the poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite film newly prepared in this example and after being placed in the air for 3 months. At 300K, the poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite film shows typical hysteresis characteristics and exhibits ferromagnetism, and its out-of-plane saturation magnetization is about 80emu.g -1 , which is much higher than the reported magnetic properties of poly(3-hexylthiophene). After aging treatment, the magnetic properties of poly(3-hexylthiophene) / fullerene / 4”-n-pentyl-4-cyanoterphenyl composite film decreased to a certain extent, but still had a high saturation magnetization of 60emu.g -1 .

[0044] Example 4

[0045] P3HT powder with a purity of 98% was weighed and dissolved in o-dichlorobenzene solvent, and then ultrasonically dissolved and mixed to obtain a 10 mg / mL poly(3-hexylthiophene) / o-dichlorobenzene solution A. Then, a certain amount of acetonitrile (VCAN :V o-DCB =15%), and after being uniformly mixed by ultrasonic treatment, the mixture was allowed to stand at room temperature to obtain a poly(3-hexylthiophene) solution B.

[0046] A certain amount of fullerene was added to solution B, with a mass ratio of fullerene to poly(3-hexylthiophene) of 1:4.5. After ultrasonic treatment and uniform mixing, the mixture was allowed to stand at room temperature to obtain poly(3-hexylthiophene) / fullerene solution C. The silicon wafer substrate was ultrasonically washed in isopropyl ether for 15 minutes, and then dried in a vacuum oven at low temperature for later use. Solution C was drop-coated on a clean substrate, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene composite charge transfer film D.

[0047] A 5 ml volume of 4"-n-pentyl-4-cyano terphenyl was used for subsequent doping, covered with a watch glass, and slowly dried at room temperature to obtain a poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyano terphenyl composite film.

[0048] The specification and drawings of the present invention are considered to be illustrative rather than restrictive. On the basis of the present invention, those skilled in the art can make some substitutions and modifications to some of the technical features according to the disclosed technical content without creative labor, all of which are within the protection scope of the present invention.

Claims

1. A method for preparing a high-performance pure organic magnetic composite material, characterized in that: The following steps are involved: S1, pre-treating poly(3-hexylthiophene) powder, o-dichlorobenzene and acetonitrile with a solvent to obtain a poly(3-hexylthiophene) solution, and then adding fullerene to obtain a mixed solution; S2, prepare a silicon wafer substrate, and clean the silicon wafer with a polar solvent; drop the mixed solution in S1 on the cleaned silicon wafer substrate, cover it with a watch glass, and slowly dry it to obtain a poly (3-hexylthiophene) / fullerene composite charge transfer film; S3: The poly(3-hexylthiophene) / fullerene composite charge transfer film obtained in S2 is subsequently doped with 4"-n-pentyl-4-cyanoterphenyl to obtain a poly(3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite material.

2. The preparation method according to claim 1, characterized in that: In S1, poly(3-hexylthiophene) powder is dissolved in o-dichlorobenzene, and the mixture is ultrasonically dissolved and mixed to obtain a poly(3-hexylthiophene) / o-dichlorobenzene solution, and acetonitrile is added to obtain a poly(3-hexylthiophene) solution.

3. The preparation method according to claim 2, characterized in that: The poly(3-hexylthiophene) powder has a purity of 95-99%.

4. The preparation method according to claim 2, characterized in that: The concentration of the poly(3-hexylthiophene) / o-dichlorobenzene solution is 5-50 mg / mL.

5. The preparation method according to claim 2, characterized in that: The volume ratio of the acetonitrile to the poly(3-hexylthiophene) / o-dichlorobenzene solution is 5%-25%.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the poly(3-hexylthiophene) powder to the fullerene in the S1 is 10:1 to 1:

1.

7. The preparation method according to claim 1, characterized in that: The polar solvent in S2 is one of ethanol, isopropanol and acetone.

8. The preparation method according to claim 1, characterized in that: The volume ratio of the poly(3-hexylthiophene) / fullerene composite charge transfer film to 4″-n-pentyl-4-cyanoterphenyl in S3 is 1:1 to 1:

10.

9. A high-performance pure organic magnetic composite material obtained by the preparation method according to any one of claims 1 to 8, wherein the high-performance pure organic magnetic composite material is a poly (3-hexylthiophene) / fullerene / 4"-n-pentyl-4-cyanoterphenyl composite material.

Citation Information

Patent Citations

  • Method for preparing poly(3-hexylthiophene) (P3HT) oriented ordered film through solution deposition

    CN102786703A

  • Method for increasing performance of metallofullerene single-molecular magnet

    CN106486239A

  • Preparation method of fullerene square lamellar crystal / polymer composite material

    CN106633733A